Interpersonal Influences on Late Adolescent Girls’ and Boys’ Disordered Eating - Shomaker, Lauren B. (2009)
Perceived socio-cultural pressure to be thin has an important impact on disordered eating during early and middle adolescence, but less is known about late adolescence. Most prospective studies included only girls, and less is known about the influence on boys. This study investigated interpersonal influences on changes in late adolescent boys’ and girls’ symptoms of disordered eating over one year. Participants were a community sample of late adolescents 16–19 years of age (N = 199; 49.75% girls), their mothers, and friends. Structural equation modeling revealed that interpersonal pressure to be thin and criticism about appearance predicted increases in disordered eating over time. Late adolescents’, mothers’ and friends’ reports of pressure were associated with disordered eating at Time 1 and Time 2. Further, adolescents’ perceptions and friends’ reports of pressure to be thin predicted changes in disordered eating over time. Findings underscore the significance of interpersonal relationships for disordered eating during late adolescence in both girls and boys.